Advancing sustainability in urban transportation: A solar-powered metro rail system. - Amam Hossain Bagdadee; Ishtiak Al Mamoon; Deshinta Arrova Dewi; Vijayakumar Varadarajan; Li Zhang; Arghya Uthpal Mondal (PLoS ONE)
This study demonstrates that solar power integration in metro rail systems is feasible to enhance urban sustainability. Solar-powered metro rail systems provide a sustainable alternative to conventional grid-powered transit by decreasing dependence on fossil fuels, lowering carbon footprints, and reducing environmental impacts. The paper analyzes design and technical constraints emphasizing the potential to use solar power to improve urban transport infrastructure with cleaner and more resilient alternatives. The resulting multi-disciplinary findings, across all relevant aspects of urbanization, provide data-driven insights and recommendations for authorities in urban planning and transportation decision-making processes, ultimately fostering the development of sustainable and livable cities for the present and future generations.